Fighting on the Ocean Blue: New Zealand's Extra-Territorial Jurisdiction and Maritime Protest - Smith, Timothy (Victoria University of Wellington Law Review, 2001)
In this article the author discusses New Zealand's extraÂterritorial jurisdiction over criminal acts which occur in the course of protest on the high seas. In particular, the jurisdictional provisions of the Crimes Act 1961 and the Maritime Crimes Act 1999 are analysed for consistency with international norms and for their value in deterring incidents of violence. The author concludes that, while imperfect, the current structure for asserting extraÂterritorial jurisdiction is perhaps the most convenient given the uncertainty inherent in jurisdictional assertions.